The Historical Development of Islamic Educational Institutions and Its Implications for Indonesia's Education System - Ighfirli Ilyas; Abdul Rosyid Teguhdin Hamid (Manunggal Halim Jaya, 2026)
The prominent role of religious organizations such as Muhammadiyah and Nahdlatul Ulama, the establishment of the Ministry of Religious Affairs in 1946, and the adoption of strategic policies—including the 1975 Joint Decree of the Three Ministers, Law No. 20 of 2003, and Law No. 18 of 2019—have provided formal legitimacy and strengthened the position of Islamic education. These developments have had far-reaching implications. Islamic education is now recognized as an integral and equal component of the national education system, plays a crucial role in shaping the nation's character and morality, and serves as a foundation for integrating general and religious knowledge. Nevertheless, Islamic education continues to face structural inequalities, including limited funding for nonformal religious education, particularly Madrasah Diniyah Takmiliyah (MDT) and Qur'anic Education Institutions (LPQ); compensation for nonpermanent teachers that remains below the regional minimum wage; inadequate pesantren infrastructure; and discrimination against madrasah graduates in admissions to public universities. Strong political commitment and equitable budget allocations are therefore necessary for Islamic education to fulfill its potential as a center for cultivating the moral character of Indonesia's younger generation and advancing the vision of Golden Indonesia 2045.